Aligning Assessment and Curriculum: A Study of Summative Tests in Educational Settings - Tiana, Ella Aprilia; Maruf, Nirwanto (JET ADI BUANA, 2024)
The study aims to explore the alignment between English summative tests and prescribed learning objectives within curriculum documents, highlighting areas of both conformity and inconformity. Employing meticulous analysis, the research identifies instances where test content aligns with specified learning objectives, while also pinpointing discrepancies or deviations. Through qualitative analysis, the study examines the degree of alignment between test content and prescribed objectives. The findings underscore numerous instances of alignment, particularly among test items correlating directly with prescribed topics and skills. Nevertheless, the research also uncovers areas of incongruity, indicating potential gaps in the assessment process. This study emphasizes the significance of rigorous test design and validation procedures to ensure that summative assessments accurately reflect intended curriculum standards and effectively measure student learning outcomes within the Merdeka curriculum context.